Effect of Source-Sink Manipulation on Photosynthetic Characteristics of Flag Leaf and the Remobilization of Dry Mass and Nitrogen in Vegetative Organs of Wheat - Ying-hua ZHANG (Journal of Integrative Agriculture, 2014)
The photosynthetic characteristics of flag leaf and the accumulation and remobilization of pre-anthesis dry mass (DM) and nitrogen (N) in vegetable organs in nine wheat cultivars under different source-sink manipulation treatments including defoliation (DF), spike shading (SS) and half spikelets removal (SR) were investigated. Results showed that the SS treatment increased the photosynthetic rate (Pn) of flag leaf in source limited cultivar, but had no significant effect on sink limited cultivar. The SR treatment decreased the Pn of flag leaf. Grain DM accumulation was limited by source in some cultivars, in other cultivars, it was limited by sink. Grain N accumulation was mainly limited by source supply. The contribution of pre-anthesis dry mass to grain yield from high to low was stem, leaf and chaff, while the contribution of pre-anthesis N to grain N from high to low was leaf, stem and chaff. Cultivars S7221 and TA9818 can increase the contribution of remobilization of DM and N to grain at the maximum ratio under reducing source treatments, which may be the major reason for these cultivars having lower decrease in grain yield and N content under reducing source treatments.